Molecular Evolutionary Analysis of a-Defensin Peptides in Vertebrates - Rahman, Arafat; Islam, M Sahidul; Saha, Otun; Saha, Titon Chandra (Rajshahi University Journal of Science and Engineering, 2016)
?-Defensin is a group of polypeptides with antimicrobial activity found in the host defense system and it is widely distributed in, but not limited to mammalian epithelial cells and phagocytes. These molecules protect the organism from a diverse spectrum of bacteria, viruses, fungi, and protozoan parasites. Different studies have revealed widesequence variation within ?-defensin sequences, but the underlying evolutionary cause is not well-studied. In this study, the ?-defensin gene from 25 vertebrate species has been comprehensively collected and computationally analyzed. NCBI gene and nucleotide databases were accessed to extract meta-information about ?-defensin gene's defensin domain and leader propeptide sequences. Full coding sequences downloaded from nucleotide database by splitting out intron sequence. MEGA software used to construct phylogenetic tree using Neighbor-Joining method, which indicates that ?-defensin gene evolution does not matches with species evolution. Selection analysis was carried out using Data Monkey web-server's FEL, SLAC, IFEL, MEME, TOGGLE and REL program on both propeptide and defensin super-family codon-aligned sequences to test different hypothesises. Positively selected sites were found on both propeptide and defensin domain, but the effect of negative selection pressure was higher on leader sequences. It was found that mutations in the positively selected sites of defensin domain had stabilizing effect on protein. Phyre2 web-server was used for homology modeling of selected ?-defensin genes. Structural variation is observed on ?-defensinproteins which may indicate heterogeneous structure-function relationship between species that reflects its interaction with diverse pathogens. This study provides a new perspective on the relationships among ?-defensin gene repertoires which will help to infer its evolution.